FOTOGRAFIA DI STRUMENTI MUSICALI METODO DI DOCUMENTAZIONE QUOTIDIANO E PROVE ELEMENTARI DI FILOLOGIA DIGITALE - Marconi, Emanuele (Archeomatica, 2012)
Il restauro virtuale, inteso come manipolazione 2d di un'immagine attraversoprogrammi di grafi ca o elaborazione digitale, può essere, in alcuni casi, unvalido aiuto per la ricerca ontologica per ottenere una visione di insieme diun'opera prima di un intervento di restauro o per ricostruire parti che non sonopervenute. In alcuni casi la manipolazione dell'immagine diviene un supporto perla ricerca organologica. Digital photo of musical instruments Digital photography is a great support in musical instruments conservation forms filling. Video documentation, still not much used, contributes a great amount of details that doesn't written text or still images. Digital image manipulation,or virtual restoration (defined as the manipulation of 2D image through digital imaging processing), in some cases can be a great help to get a fi rst overview of a restoration, or to reconstruct parts of an artwork that are missed. Some case studies are presented, showing differents application ofsimple techniques to on the field activities regarding musical instruments.